A real‐time pluvial flood forecasting system for Castries, St. Lucia. (18th September 2015) - René, J.‐R.; Djordjević, S.; Butler, D.; Mark, O.; Henonin, J.; Eisum, N.; Madsen, H.
Abstract: In the last decade, real‐time flood forecasting has become a more feasible approach to reducing the impacts of flooding in urban areas. Two key tools in this context are high resolution hydrodynamic modelling in combination with accurate hydrological forcing. In some cases, when it is not possible to produce such accurate flood forecasts based on high resolution models and data, it may nevertheless be possible to use the resources currently available, accepting that there is a greater degree of uncertainty involved. This paper demonstrates the feasibility of a remotely controlled, real‐time, pluvial flood forecasting system for Castries, St. Lucia that utilises the limited data available locally. The results from the study suggest that although Global Forecast System (GFS) rainfall data may be considered coarse for urban applications, there is still a significant amount of skill and usability after it is postprocessed and used in combination with observed rainfall data. Evidence from the study also suggests that the use of images from different sources is invaluable for 2D overland model calibration and validation in urban areas. Conclusions from the study are potentially transferable to other sites in similar data‐scare and resource‐limited locations.